2017
DOI: 10.25133/jpssv26n1.006
|View full text |Cite
|
Sign up to set email alerts
|

Child Labor and Its Effects on Schooling, Health and Recreation of Filipino Children

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…The findings reveal that the street children are obligated to contribute to the family by providing income to them and the children had to be independent and earn for themselves to survive. These findings reveal that the street children are exposed to work at an early age to fend for themselves and their family (Nelson & Quiton, 2018). Sometimes a child would experience physical, verbal and emotional abuse from parents when he/she returned home without income.…”
Section: Discussionmentioning
confidence: 84%
“…The findings reveal that the street children are obligated to contribute to the family by providing income to them and the children had to be independent and earn for themselves to survive. These findings reveal that the street children are exposed to work at an early age to fend for themselves and their family (Nelson & Quiton, 2018). Sometimes a child would experience physical, verbal and emotional abuse from parents when he/she returned home without income.…”
Section: Discussionmentioning
confidence: 84%
“…A child 8 in poverty could contribute to the improvement of the her or his own conditions as well as her or his parents by working, and working could be beneficial for the child and the society since it would improve individual skills, a sense of responsibility, and even support schooling by providing the financial requirements (Bourdillon, 2017).A flexible and coordinated approach could ensure school attendance and working and improve the child's performance in both spheres (Orkin, 2012). Certain studies suggested that short-term work that would not exceed 2 hours per day did not have a significant negative effect on schooling (Nelson & Quiton, 2018;Omokhodion, et al 2006;Ravallion & Wodon, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Especially when social security is not available for parents with inadequate income and several children, they require the income provided by the children to meet their basic needs and livelihood. Previous studies reported that children are employed for economic, social and cultural reasons (Nelson & Quiton, 2018). The inadequate income level of the parents is a significant factor that affects the educational lives of children (Hirsch, 2007;Demie & Lewis, 2011, Cassen & Kingdon, 2007Psacharopoulos, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Of course, if cash transfer benefits are conditioned on school attendance, even in the absence of empirical evidence, there is less reason to doubt that child labour would be low among beneficiary households. The more time children spend attending school, the less time they spend on work activities (Ravallion and Wodon, ; Beegle et al , ; Nelson and Quiton, ).…”
Section: Introductionmentioning
confidence: 99%